Credibility dan Brand Image BTS Kolaborasi Karakter BT21 Terhadap Keputusan Pembelian Chatime - Aryani, Dwi Nita; Hariyani, Bita Septiya (Business Management Journal, 2024)
The development of social media such as Instagram, Twitter and Facebook are accelerating the spread of information, photos and videos, particularly the trend related to the Korean Wave. The role of Korean influencers has big impact in creating a large and active community of fans to buy a product, as Chatime has done. BT21's characters capture the attention of consumers and generate significant purchase interest. The purpose of this study was to analyse the effect of credibility and brand image in the form of BT21 Character collaboration on consumer purchasing decisions at Chatime. The population in this study were consumers who made purchases at Chatme Malang.  The sample used in this study amounted to 100 people. The sampling technique was carried out by purposive sampling method. The data were collected by distributing questionnaires. Testing of research results was carried out using the SEM-PLS method. The results showed that credibility and brand image in the form of BT21 Character Collaboration had a significant positive effect on consumer purchasing decisions at Chatime. Thisresults contribute to enrich marketing strategy and purchasing decision theories, and also can be used by Chatime Company to consider the variables which affect customers in making decision to purchase its products. This study has limitation amit the research was held in Malang as an education city, that might it will has different results if this reseach to be done in other cities.